2022
DOI: 10.3390/foods11244077
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Changes in pH and Soluble Solids Content of Potato during the Storage by Electronic Nose and Vis/NIR Spectroscopy

Abstract: Potato is an important agricultural product, ranked as the fourth most common product in the human diet. Potato can be consumed in various forms. As customers expect safe and high-quality products, precise and rapid determination of the quality and composition of potatoes is of crucial significance. The quality of potatoes may alter during the storage period due to various phenomena. Soluble solids content (SSC) and pH are among the quality parameters experiencing alteration during the storage process. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Indeed, this result can only emphasize the influence of temperatures above 4C on the pH increase. Khorramifar et al (2022), concluded that pH variations increased slightly during the storage period, compared to…”
Section: Results and Discussion Phmentioning
confidence: 99%
“…Indeed, this result can only emphasize the influence of temperatures above 4C on the pH increase. Khorramifar et al (2022), concluded that pH variations increased slightly during the storage period, compared to…”
Section: Results and Discussion Phmentioning
confidence: 99%
“…The information fusion of E‐nose technology and spectral technology can be used for the nondestructive detection of flavored substances (Khorramifar et al., 2022). Traditional flavor detection often uses gas chromatography‐mass spectrometry (GC‐MS), capable of accurate qualitative analysis while with poor real‐time performance.…”
Section: Spectral Data Fusion Techniquesmentioning
confidence: 99%
“…SVM is a supervised learning and classification algorithm based on statistical theory (Khorramifar et al, 2022c). An SVM can nonlinearly map input data that are not linearly separable in a low-dimensional space to a highdimensional space using a kernel function.…”
Section: Chemometrics Analysis and Neural Networkmentioning
confidence: 99%